Unsettling experiences: A qualitative inquiry into young peoples’ narratives of diagnosis for common skin conditions in the United Kingdom - McNiven, Abigail; Ryan, Sara (Frontiers in Psychology, 2022)
Skin conditions such as eczema and psoriasis are relatively prevalent health concerns in children, adolescents and young adults. Experiences of these dermatology diagnoses in adolescence have hitherto not been the focus of research, perhaps owing to assumptions that these diagnoses are not particularly impactful or intricate processes, events or labels. We draw on a secondary analysis of in-depth interviews with 42 adolescents and young people living in the UK and, influenced by the sociologies of diagnosis and time, highlight the psychological, emotional, social and temporal complexities involved in their diagnosis experiences. Firstly, we describe how participants remembered, re- and co- constructed their diagnosis experiences during the interview. Secondly, we explore the pace and rhythm of diagnosis, including mis-diagnoses, highlighting the jarring potential for adolescents on being diagnosed, even for conditions typically deemed minor. Thirdly, we consider the ways in which these diagnoses have the capacity to reformulate notions of past, present and future, including projecting into imagined futures and reinterpreting past bodily sensations. Finally, we examine how memories about and the meaning of diagnosis are revisited, revised and potentially replaced as a child or adolescent grows older, and increases their management of their condition and encounters with healthcare professionals. In unsettling an assumption that diagnosis experiences for adolescents of common skin conditions is unproblematic or straightforward, our qualitative analysis critically engages with and contribute to tenets of health research that are of interest to quantitative and qualitative researchers, clinicians and patients.